Transfer of the symbiotic plasmid of rhizobium etli CFN42 to endophytic bacteria inside nodules - Bañuelos Vazquez, Luis Alfredo (2020)
Conjugative transfer is one of the mechanisms allowing diversification and evolution ofbacteria. Rhizobium etli CFN42 is a bacterial strain whose habitat is the rhizosphere andis able to form nodules as a result of the nitrogen-fixing symbiotic relationship it mayestablish with the roots of Phaseolus vulgaris. R. etli CFN42 contains one chromosomeand six large plasmids (pRet42a ? pRet42f). Most of the genetic information involvedin the establishment of the symbiosis is localized on plasmid pRet42d, named asthe symbiotic plasmid (pSym). This plasmid is able to perform conjugation, usingpSym encoded transfer genes controlled by the RctA/RctB system. Another plasmidof CFN42, pRet42a, has been shown to perform conjugative transfer not only in vitro,but also on the surface of roots and inside nodules, using other rhizobia as recipients.In addition to the rhizobia involved in the formation of nodules, these structures havebeen shown to contain endophytic bacteria from different genera and species. Inthis work, we have explored the conjugative transfer of the pSym (pRet42d) fromR. etli CFN42 to endophytic bacteria as putative recipients, using as donor a CFN42derivative labeled with GFP in the pRet42d and RFP in the chromosome. We wereable to isolate some transconjugants, which inherit the GFP, but not the RFP marker.Some of them were identified, analyzed and evaluated for their ability to nodulate.We found transconjugants from genera such as Stenotrophomonas, Achromobacter,and Bacillus, among others. Although all the transconjugants carried the GFP marker,and nod, fix, and nif genes from pRet42d, not all were able to nodulate. Ultrastructuremicroscopy analysis showed some differences in the structure of the nodules of one ofthe transconjugants. A replicon of the size of pRet42d (371 Kb) could not be visualizedin the transconjugants, suggesting that the pSym or a segment of the plasmid isintegrated in the chromosome of the recipients. These findings strengthen the proposalthat nodules constitute a propitious environment for exchange of genetic informationamong bacteria, in addition to their function as structures where nitrogen fixation andassimilation takes place